The influences of positive end expiratory pressure (PEEP) associated with physiotherapy intervention in phase I cardiac rehabilitation (Clinics, 2005)
PURPOSE: To evaluate the effects of positive end expiratory pressure and physiotherapy intervention during Phase I of cardiac rehabilitation on the behavior of pulmonary function and inspiratory muscle strength in postoperative cardiac surgery. METHODS: A prospective randomized study, in which 24 patients were divided in 2 groups: a group that performed respiratory exercises with positive airway expiratory pressure associated with physiotherapy intervention (GEP, n = 8) and a group that received only the physiotherapy intervention (GPI, n = 16). Pulmonary function was evaluated by spirometry on the preoperative and on the fifth postoperative days; inspiratory muscle strength was measured by maximal inspiratory pressure on the same days. RESULTS: Spirometric variables were significantly reduced from the preoperative to the fifth postoperative day for the GPI, while the GEP had a significant reduction only for vital capacity (P < .05). When the treatments were compared, smaller values were observed in the GPI for peak flow on the fifth postoperative day. Significant reductions of maximal inspiratory pressure from preoperative to the first postoperative day were found in both groups. However, the reduction in maximal inspiratory pressure from the preoperative to the fifth postoperative day was significant only in the GPI (P < .05). CONCLUSIONS: These data suggest that cardiac surgery produces a reduction in inspiratory muscle strength, pulmonary volume, and flow. The association of positive expiratory pressure with physiotherapy intervention was more efficient in minimizing these changes, in comparison to the physiotherapy intervention alone. However, in both groups, the pulmonary volumes were not completely reestablished by the fifth postoperative day, and it was necessary to continue the treatment after hospital convalescence.